2015
DOI: 10.1007/s10585-015-9694-5
|View full text |Cite
|
Sign up to set email alerts
|

HER2 and β-catenin protein location: importance in the prognosis of breast cancer patients and their correlation when breast cancer cells suffer stressful situations

Abstract: In human breast cancer, β-catenin localization has been related with disease prognosis. Since HER2-positive patients are an important subgroup, and that in breast cancer cells a direct interaction of β-catenin/HER2 has been reported, in the present study we have explored whether β-catenin location is related with the disease survival. The study was performed in a tumor bank from patients (n = 140) that did not receive specific anti-HER2 therapy. The proteins were detected by immunohistochemistry in serial sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…[9][10][11] Our results show that PAI-1, ADAM12, and β-catenin are more abundant in advanced stages compared to primary tumors. Our results correlated with in vivo and in vitro studies conducted previously [12][13][14] using cells and tumor tissues.…”
Section: Discussionsupporting
confidence: 91%
“…[9][10][11] Our results show that PAI-1, ADAM12, and β-catenin are more abundant in advanced stages compared to primary tumors. Our results correlated with in vivo and in vitro studies conducted previously [12][13][14] using cells and tumor tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Upon Wnt ligand engagement, β-catenin is activated and disrupted, followed by its translocation from the cytoplasm into the nucleus, where it facilitates the transcription of genes involved in EMT, such as Twist, Snail, Slug, which repress the expression of E-cadherin, influencing cell junction and polarity (37). Previous studies have reported that overexpression and hyperactivation of β-catenin are observed in aggressive basallike breast cancer, and are positively correlated with poor patient clinical outcome (38)(39)(40). Therefore, β-catenin may be a novel therapeutic target with which to overcome breast cancer metastasis and improve the prognosis of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not detect a correlation between the intensity of β-catenin expression and the survival period of CMT patients (data not shown). Concerning the inconsistencies among previous reports on the correlation between the expression and subcellular location of β-catenin and the prognosis of human breast cancer and CMTs [ 3 4 13 14 ], further studies are required to understand the roles played by β-catenin in the tumorigenesis and tumor progression of CMTs.…”
Section: Discussionmentioning
confidence: 99%